On the Border : Ethics and the Face in Contemporary Israeli Cinema - Zanger, Anat (MiKAN, 2013)
In what sense does an observing and documenting camera constitute an authority which contributes to a spatial dialogue and ethical discourse? Sites of transition such as borders, airports, and checkpoints serve as a contact point between military and policing authorities and the heterogeneous civilian population. In Israeli cinema, the presence of those sites provides an intersection between the physical-territorial and the cinematic image. This article focuses on the various modes with which the camera challenges the physical border demarcated by control points in order to gain access to the face of the “I” and the “other”. Following the French-Jewish philosopher Emmanuel Levinas, the article identifies the face of the other as a catalyst of interpersonal contact and proximity. Four contemporary Israeli films are explored: the short fiction film Ben Gurion (Gil Levenberg, 1997) and the documentaries Borders (Eran Riklis and Nurit Kedar, 1999), Checkpoints (Yoav Shamir, 2003) and Avenge but One of my Two Eyes (Avi Mograbi, 2005).